2021
DOI: 10.3390/socsci10100401
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Barometer 2020: Attitudes towards Immigration and Ethnic Diversity in Sweden

Abstract: Migration is topical in many counties, and attitudes towards immigration and ethnic diversity are volatile. In our longitudinal “Diversity Barometer”, we have studied changes in Swedes’ attitudes towards immigration and ethnic diversity in Sweden since 2005, using a postal questionnaire sent to a random sample of the Swedish population aged 18–75. In this article, we analyzed data from 2020 (n = 1035) in comparison with previous Diversity Barometer surveys from 2005 to 2018. The findings showed that Swedes had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Findings show that 67% of people who never interact with immigrants from non-European countries are negative or indifferent towards diversity compared to 37% who interact with immigrants weekly (Figure 7). Additional findings from the Diversity Barometer indicate that younger people and those with higher education, i.e., groups with a higher chance to interact with immigrants have more positive experiences of working or studying with immigrants (Munobwa et al 2021). The younger generations and people who have studied at university seem to base their attitudes on their lived experiences rather than stereotypes and prejudices.…”
Section: Spatial Segregationmentioning
confidence: 96%
“…Findings show that 67% of people who never interact with immigrants from non-European countries are negative or indifferent towards diversity compared to 37% who interact with immigrants weekly (Figure 7). Additional findings from the Diversity Barometer indicate that younger people and those with higher education, i.e., groups with a higher chance to interact with immigrants have more positive experiences of working or studying with immigrants (Munobwa et al 2021). The younger generations and people who have studied at university seem to base their attitudes on their lived experiences rather than stereotypes and prejudices.…”
Section: Spatial Segregationmentioning
confidence: 96%
“…The Middle Eastern minority in Sweden currently constitutes $6.24% of the total population (Statistiska centralbyrån [SCB], n.d.) and as of 2019, the two most represented countries for individuals born outside of Sweden were Syria and Iraq (Burström, 2019). Although attitudes toward ethnic diversity and immigration have improved compared to the peak of the migrant influx, they remain negative in comparison to pre-crisis levels (Munobwa et al, 2021). Failed integration and increased diversity have also been noted as a potential challenge to social cohesion in Sweden and as early as 2009 it was reported that 45% of Swedes felt that there were "severe tensions" between ethnic groups in Sweden (Commission on the Future of Sweden, 2013, p. 218).…”
Section: The Research Context Of Swedenmentioning
confidence: 99%